A systematic review of interventions to improve adherence to anti-diabetic medications in patients with type 2 diabetes in sub-Saharan Africa - Iyun, Oluwatosin Busola (Department of Public Health and Family Medicine, 2023)
Background: Diabetes Mellitus is a worldwide public health issue that affects millions of people. It is among the ten-leading causes of death worldwide. In 2019, the International Diabetes Federation projected that 463 million adults had diabetes and 4.2 million died from the disease and its complications. Given that diabetes can be effectively controlled with education, counselling, and the adaptation of healthy lifestyles, as well as drug therapy, the number of deaths is high. Increasing evidence of alarmingly low adherence rates, which limit clinical benefits, suggests that improving the effectiveness of adherence interventions can impact public health much better than any advancement in definitive medical therapies. The World Health Organisation has strongly supported the recommendations for evaluating the effectiveness of health interventions in practice, especially those addressing adherence. Methods: This is a systematic review that aims to undertake a quantitative review of interventions to improve adherence to anti-diabetic medications for adults with type 2 diabetes in subSaharan Africa, and the impact of these interventions in achieving good glycaemic control. For the evaluation of these interventions, only randomized controlled trials will be considered. We will perform electronic searches of all published papers available on PubMed. The reference lists of all relevant articles, abstracts, and conference published records will be manually searched. A search of Grey literature sites such as Google and Google scholar, as well as the Networked Digital Library of Theses and Dissertations, will be undertaken. A data extraction form will be used. All studies will be screened by two independent reviewers for articles that meet the inclusion criteria. Relevant data will be extracted, and the methodological quality of all included studies will be assessed based on selection, performance, attrition, detection, and reporting biases. We will perform a meta-analysis on the included studies. The statistical heterogeneity in the included studies will be determined using the Chi-squared test (χ2) test of homogeneity and quantified using I 2 statistic. A narrative summary of findings will be presented if data is too heterogeneous. Discussion: This review will provide evidence to assist policymakers and public health experts in making decisions and prioritizing effective interventions that have been identified.